Investigation of Hand Injuries During Turnaround Based on Job Hazard Analysis - NORMAN, NOREEN SYAKIREEN; YASAK, FUAD (Progress in Engineering Application and Technology, 2023)
This study aims to determine the rate of accidents involving hand injuries in servicing valves in the oil and gas industry. This study will be conducted at MRCSB’s Plant 1 (area 4). Three objectives have been listed in Chapter 1: to investigate the root cause of accidents related to the work process during turnaround, to analyse hand injuries accident based on past data accidents during turnaround, and to recommend control measures for reducing hand injuries based on the hazard. This method determines the total data of accidents in the service valve and the total data from the contribution of hand injuries during the turnaround in 2019 and 2022. From the comprehensive data on accidents, 141 accidents happened, and 41 cases were from hand injury accidents. A method of Job Hazard Analysis (JHA) has been applied to know the hazard and the risk rating of each work activity. In summary, Job Hazard Analysis is one of the control measures being proposed and developed that are required for the safety and health worker to work in a safe condition.